NATIONAL HEALTH INSURANCE: AN EXPLORATORY STUDY OF PATIENT SATISFACTION - Nihayatul Munaa (Indonesian Journal of Health Care Management, 2020)
Background:Indonesia has been implemented National Health Insurance since 2014 and was targeted to achieve Universal Health Coverage by 2019 through quality improvement and cost efficiency strategy. However, the little understanding of this new policy leads to an increase of complaint in the hospital as a health care provider.Purpose: This study seeks to understand the factors that might influence a patient's perception of National Health Insurance in Indonesia.Method: This is a descriptive observational study with a cross-sectional design method. Data was collected through in-depth interview with 96 patient from Jemursari Islamic Hospital of Surabaya (RumahSakit Islam Jemursari Surabaya) who participate in National Health Insurance. The subject was selected by simple random sampling.Results: The findings demonstrated that from five categories, 82,3% patient was satisfied in the reliability aspect and 85,4% in assurance aspect, while intangible, responsiveness and empathy aspect >90% patient was satisfied. Meanwhile, in Indonesia, the minimum service standard of healthcare for patient satisfaction is 90%.Conclusion:Health providers must understand the patient's value and preference and do a service based on their value.